Mitochondrial Function as Related to Psychological Distress in Health Care Professionals - Gaetani, Simona; Galzignati, Luca; Marcati, Michela; Durazzi, Paola; Cianella, Adalgisa; Mocheggiani, Valentina; Monaco, Federica; Bracci, Massimo; Neuzil, Jiri; Tomasetti, Marco; Amati, Monica; Santarelli, Lory (Psychosomatic medicine, 2022)
OBJECTIVE: The present study evaluated the association of psychological distress and radiation exposure as a work-related stressor with mitochondrial function in health care professionals. METHODS: Health care professionals at a regional hospital in Italy were evaluated for physical health and psychological measures using self-report questionnaires (n = 41; mean age = 47.6 [13.1] years; 66% women). In a second sample, individuals exposed to elevated levels of ionizing radiation (IR; likely effective dose exceeding 6 mSv/y; n = 63, mean age = 45.8 [8.8] years; 62% women) were compared with health care workers with low IR (n = 57; mean age = 47.2 [9.5] years; 65% women) because exposure to a toxic agent might act as a (work-related) stressor. Associations were examined between psychological factors (12-item General Health Questionnaire, Perceived Stress Scale), work ability (Work Ability Index), and IR exposure at the workplace with markers of mitochondrial function, including mitochondrial redox activity, mitochondrial membrane potential, mitochondrial DNA (mtDNA) copy number, biogenesis, and mtDNA damage response measured from peripheral blood mononuclear cells. RESULTS: All participants were in good physical health. Individuals reporting high levels of psychological distress showed lower mitochondrial biogenesis as indicated by peroxisome proliferator-activated receptor-γ coactivator 1-α and lower nuclear factor erythroid 2-related factor 2 (NRF2) expression (2.5 [1.0] versus 1.0 [0.9] relative expression [rel exp], p = .035, and 31.5 [5.0] versus 19.4 [6.9] rel exp, p = .013, respectively). However, exposure to toxic agents (IR) was primarily associated with mitochondrial metabolism and reduced mtDNA integrity. Participants with IR exposure displayed higher mitochondrial redox activity (4480 [1202] mean fluorescence intensity [MFI]/min versus 3376 [983] MFI/min, p < .001) and lower mitochondrial membrane potential (0.89 [0.09] MFI versus 0.95 [0.11] MFI, p = .001), and reduced mtDNA integrity (1.18 [0.21] rel exp versus 3.48 [1.57] rel exp, p < .001) compared with nonexposed individuals. CONCLUSIONS: This study supports the notion that psychological distress and potential stressors related to toxic agents might influence various aspects of mitochondrial biology, and that chronic stress exposure can lead to molecular and functional recalibrations among mitochondria.
Keywords: Mitochondria; Psychological Distress; DNA, Mitochondrial; leukocyty mononukleární; Female; Leukocytes, Mononuclear; Health Personnel; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; zdravotnický personál; lidé středního věku; mitochondrie; Middle Aged; mitochondriální DNA; psychický distres